In the Process of Forming a Person, Overcoming the Emotional State in The Family Environment (Eurasian Journal of Humanities and Social Sciences, 2022)
The process of personal development, individual psychological characteristics, the influence of social environment. Stability of the family environment, overcoming emotional states, creating a psychological climate for a healthy life style in the family.